COST BENEFIT ANALYSIS OF IMPLEMENTING VACUUM FRYING TECHNOLOGY IN PROCESSING RESISTANT CATFISH (CASE STUDY OF BARENGKRAJAN VILLAGE, SIDOARJO) - Gama Tengtarto, Jaya Adi; As Syukri, Khoirul Anam; Rosidin, Mochammad Khoirul; Ekasari, Ratna; Yucha, Nikma; Sifa'uddin, Muhammad Nur; Aji Wibowo, Sasongko (Universitas Maarif Hasyim Latif, 2024)
The application of vacuum frying technology in the processing of discarded catfish has great potential to increase the economic value of products that have been considered less valuable. This study aims to conduct a cost-benefit analysis of the application of this technology in Barengkrajan Village, Sidoarjo, with a focus on improving product quality, reducing waste, and increasing income for the local community. The research methods used include financial and technical analysis and conducting interviews with some of the required data. Based on the research conducted on the application of vacuum frying machines or vacuum frying machines, several values ????are obtained from the investment feasibility criteria based on Cost Benefit Analysis. The NPV value of the catfish chips industry that has been calculated annually is Rp. 91,754,333 with an interest rate of 6% and an investment period of 10 years with an initial capital of Rp. 53,287,000 is Rp. 622,951,104, -. In addition, the calculation of the Internal Rate of Return (IRR) expressed in% shows the results of the IRR calculation of the catfish chips industry obtained a value of 45.3%. This means that the business meets the criteria for investment feasibility. For the Pay Back Period (PBP) of the catfish chips industry is 6.97 months or 209 days. This means that the business will return its capital before 1 year has passed. While the Break Event Point (BEP) is based on the calculation of the number of units that need to be sold to get the break-even point of the catfish chips product, which is 672 pcs/year or IDR 8,736,000/year. Meanwhile, the Sensitivity analysis of the catfish chips product shows that when the BEP (fixed costs) increases twofold, the annual net profit and NPV of the business decrease. The NPV before the increase in BEP was IDR 558,049,128, while the NPV after the increase in BEP was IDR 491,787,560, with a decrease in NPV of around IDR 66,261,568. Based on the calculation results, it shows that the catfish chips industry by implementing a vacuum frying machine is said to meet investment feasibility